Family Development to Create Family Resilience - Rila Kusumaningsih (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Family development is carried out to create quality and prosperous families who live in a healthy environment at every stage of life, so that different but sustainable interventions are needed. With efforts to carry out family development, resilience will be created in a family. Family resilience is an ability to face and manage problems in difficult situations so that family functions continue to run harmoniously, to achieve the physical well-being and inner happiness of its members. The method used by the author in making this scientific work is to socialize or present material directly to the people of the Bojong Gede village with a brief and simple explanation which can then lead to interaction bias through discussion and question and answer. This is done with the aim of providing information as well as knowledge aimed at the community in forming and creating a harmonious family and at the same time creating resilience within the family sphere.